2017
DOI: 10.1186/s13071-017-2229-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Schistosoma japonicum tetraspanning orphan receptor and its role in binding to complement C2 and immunoprotection against murine schistosomiasis

Abstract: BackgroundSchistosomiasis remains an important global public health problem, as millions of people are at risk of acquiring infection. An ideal method for sustainable control of schistosomiasis would be to develop an efficient vaccine. Schistosomes can survive in the host vascular system by immune evasion, regulating the host complement cascade. Schistosoma japonicum tetraspanning orphan receptor (SjTOR) is a complement regulator, which is a tegument membrane protein. To date there is no experimental evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Immunization with C4BP-fused MSP1 19 induced protective immunity in BALB/c mice against the otherwise lethal malarial parasitic challenge of Plasmodium yoelii , possibly through protection of the parasite from complement lysis ( Ogun et al, 2008 ). Vaccination with complement regulator CRIT ed1 synthetic peptide conferred protection against the challenge of Schistosoma japonicum in mice through the inhibition of complement activity both in vitro and in vivo ( Ma et al, 2017 ). T. cruzi expresses a complement regulatory protein (Tc-CRP) as a major antigen that induces the production of lytic antibodies during T. cruzi infections, making it a potential target for vaccine development ( Henrique et al, 2016 ).…”
Section: Parasite-generated Complement Regulatory Proteins As Vaccinementioning
confidence: 99%
“…Immunization with C4BP-fused MSP1 19 induced protective immunity in BALB/c mice against the otherwise lethal malarial parasitic challenge of Plasmodium yoelii , possibly through protection of the parasite from complement lysis ( Ogun et al, 2008 ). Vaccination with complement regulator CRIT ed1 synthetic peptide conferred protection against the challenge of Schistosoma japonicum in mice through the inhibition of complement activity both in vitro and in vivo ( Ma et al, 2017 ). T. cruzi expresses a complement regulatory protein (Tc-CRP) as a major antigen that induces the production of lytic antibodies during T. cruzi infections, making it a potential target for vaccine development ( Henrique et al, 2016 ).…”
Section: Parasite-generated Complement Regulatory Proteins As Vaccinementioning
confidence: 99%
“…Previous research on schistosomiasis 13 and malaria 14 has demonstrated that the corresponding parasites interfere with the complement system through a variety of mechanisms, leading to diminished local inflammatory responses and progression into chronic infectious diseases. During Echinococcus granulosus (E.g) infection, the complement system is activated via the AP, and the protoscolex is thereby lysed to control parasitic infection.…”
Section: Introductionmentioning
confidence: 99%